Penerapan Manajemen Layanan Bimbingan dan Konseling dalam Upaya Meningkatkan Mutu Belajar Siswa - Dewany, Rahayu; Firman; Neviyarni (Medan Resource Center, 2022)
Quality management is determined by the ability of education managers such as principals, guidance and counseling coordinators, guidance and counseling teachers, student curriculum representatives, and homeroom teachers at local schools in planning, organizing, implementing, monitoring/assessing and following up on the implementation of guidance program services. and counseling in schools. The purpose of this study was to determine how the implementation of guidance and counseling management through planning, organizing, implementing, evaluating and following up. The type of research used is a field study that examines intensively the background of the current situation and social interactions, individuals, groups, institutions and communities through observation and interview techniques. The data that has been collected is then analyzed based on the findings in the field. The results of this study indicate that the planning of guidance and counseling services is carried out optimally, the implementation is carried out by determining the services and areas of guidance, the implementation of service management is carried out through the service format and direct supervision in written and oral form. the results of observations and interviews state that through the application of guidance and counseling management can improve the quality of student learning, this is indicated by positive attitudes and study habits. Keywords: BK Service Management, Student Learning Quality